2019
DOI: 10.1016/j.tra.2018.10.042
|View full text |Cite
|
Sign up to set email alerts
|

“To support or not to support, that is the question”. Testing the VBN theory in predicting support for car use reduction policies in Russia

Abstract: High use of motorized vehicles is a major cause of CO 2 emissions, affecting the quality of the environment negatively. Employing policies that aim to reduce car use would be key to decrease transport-related emissions. However, such policies need to be accepted by the public to be successful. In the current paper, we examine whether support for car use reduction policies can be predicted by the Value-Belief-Norm theory (VBN;Stern, 2000), reflecting a process of value triggered norm-activation about reducing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 30 publications
7
53
1
4
Order By: Relevance
“…Particularly people's strong biospheric values have been found to be important to explain multiple pro-environmental behaviors (de Groot and Steg, 2007a,b;Steg et al, 2012Steg et al, , 2014Merrill et al, 2018). Studies found positive relationships between biospheric values and recycling and environmental activism (Balundë et al, 2019), energy conservation (de Groot et al, 2012;Sahin, 2013) and acceptability of policies to reduce car use (Hiratsuka et al, 2018;Ünal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly people's strong biospheric values have been found to be important to explain multiple pro-environmental behaviors (de Groot and Steg, 2007a,b;Steg et al, 2012Steg et al, , 2014Merrill et al, 2018). Studies found positive relationships between biospheric values and recycling and environmental activism (Balundë et al, 2019), energy conservation (de Groot et al, 2012;Sahin, 2013) and acceptability of policies to reduce car use (Hiratsuka et al, 2018;Ünal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Latin America, notably Argentina, biospheric values were related to household energy savings (Jakovcevic and Reyna, 2016), and intention to reduce passenger car use and acceptability of passenger car taxation policies (Jakovcevic and Steg, 2013). In addition, biospheric values were related to energy conservation behavior in Hungary (De Groot et al, 2012) and Turkey (Sahin, 2013), and acceptability of car use reduction policies in Japan and Russia (Hiratsuka et al, 2018; Ünal et al, 2019). These studies however did not include environmental self-identity.…”
Section: Introductionmentioning
confidence: 99%
“…In a later study, the same connection between problem awareness and acceptability was identified, concluding that increasing problem awareness may increase acceptability of various traffic measures [21]. A more recent study found not only that problem awareness was related to a stronger sense of responsibility to reduce harmful actions, and hence a greater acceptability of traffic-reducing measures, but that environmental concern was the strongest predictor of problem awareness [28]. Here, too, the VBN theory plays an important role, with different values influencing an individual's perception of environmental problems.…”
Section: Factors Influencing Acceptability Of Environmental Transportmentioning
confidence: 67%
“…(1) Personal norm, often underlined by environmental beliefs or biospheric values, appears to be one common predictor of acceptability of car use reduction policies, particularly following the value-belief-norm (VBN) theory [27]. A person's moral obligation, and hence their willingness, to reduce their car use seems to be driven by an awareness that their actions cause harm to the environment [10,12,20,28].…”
Section: Factors Influencing Acceptability Of Environmental Transportmentioning
confidence: 99%
See 1 more Smart Citation